Peningkatan Kemampuan Berpikir Kreatif Mahasiswa melalui Model Inquiry Terbimbing pada Materi Pembiasan Cahaya dalam Kegiatan Lesson Study - M. Fadhil Raga Ananda; Kelvin; Sampe Hamonangan Turnip; Nova Susanti; Neneng Lestari (Universitas Nurul Huda, 2026)
This study aims to improve the creative thinking skills of prospective physics teachers through the implementation of Guided Inquiry–based Lesson Study on the topic of light refraction. The research subjects were seventh-semester Physics Education students at Universitas Jambi who participated in one Lesson Study cycle consisting of the plan, do, and see stages. The Guided Inquiry model was integrated into learning activities to develop four indicators of creative thinking: fluency, flexibility, originality, and elaboration. Data were collected through observation sheets, student worksheets, assessment results, and reflection notes, and analyzed using the Teaching–Learning-Based Analysis (TBLA). The results indicate an improvement in students’ creative thinking skills, with an average score of 3.57 (high category), particularly in flexibility and elaboration. Collaborative reflection among the model teacher, observers, and lecturer contributed to improved lesson design and increased student participation. Therefore, Guided Inquiry–based Lesson Study is effective in fostering creative and reflective thinking skills of prospective physics teachers.